Rapamycin activates mammalian microautophagy - Masahiro Sato; Takahiro Seki; Ayumu Konno; Hirokazu Hirai; Yuki Kurauchi; Akinori Hisatsune; Hiroshi Katsuki (Elsevier, 2019)
Autophagy-lysosome proteolysis is classified into macroautophagy (MA), microautophagy (mA) and chaperone-mediated autophagy (CMA). In contrast to MA and CMA, mA have been mainly studied in yeast. In 2011, mammalian mA was identified as a pathway to deliver cytosolic proteins into multivesicular bodies. However, its molecular mechanism is quite different from yeast mA. Using a cell-based method to evaluate mA and CMA, we revealed that rapamycin, an activator of yeast mA, significantly activated mammalian mA. Although rapamycin activates MA, mA was also activated by rapamycin in MA-deficient cells. These findings suggest that rapamycin is a first-identified activator of mammalian mA. Keywords: Microautophagy, Chaperone-mediated autophagy, Rapamycin